Impact of treatment strategies on cephalosporin and tetracycline resistance gene quantities in the bovine fecal metagenome - Kanwar, Neena; Scott, Harvey Morgan; Norby, Bo; Loneragan, Guy H.; Vinasco-Torres, Javier; Cottell, Jennifer L.; Chalmers, Gabhan; Chengappa, Muckatira M.; Bai, Jianfa; Boerlin, Patrick (My University, 2014)
The study objective was to determine the effects of two treatment regimens on quantities of ceftiofur and tetracycline resistance genes in feedlot cattle. The two regimens were ceftiofur crystalline-free acid (CCFA) administered to either one or all steers within a pen and subsequent feeding/not feeding of therapeutic doses of chlortetracycline. A 26-day randomized controlled field trial was conducted on 176 steers. Real-time PCR was used to quantify bla[subscript CMY-2], bla[subscript CTX-M], tet(A), tet(B), and 16S rRNA gene copies/gram of feces from community DNA. A significant increase in ceftiofur resistance and a decrease in tetracycline resistance elements were observed among the treatment groups in which all steers received CCFA treatment, expressed as gene copies/gram of feces. Subsequent chlortetracycline administration led to rapid expansion of both ceftiofur and tetracycline resistance gene copies/gram of feces. Our data suggest that chlortetracycline is contraindicated when attempting to avoid expansion of resistance to critically important third-generation cephalosporins.
Keywords: Chlortetracycline; Ceftiofur resistance; Tetracycline resistance